Gorgonians Are Foundation Species on Sponge-Dominated Mesophotic Coral Reefs in the Caribbean - Marc Slattery; Michael P. Lesser (Frontiers in Marine Science, 2021)
Foundation species (FS) regulate ecological processes within communities often facilitating biodiversity and habitat complexity. Typically FS are dominant structure-forming taxa; but less dominant taxa having disproportionate ecological impacts to the community can also be FS. Mesophotic coral ecosystems (MCEs) are deep coral reef (∼30–150 m) communities, often dominated by emergent sponges in the Caribbean Basin. Despite the potential competitive advantage of sponges on MCEs, gorgonians are also common constituents of these reefs. Data from the Bahamas demonstrate increased biodiversity and densities of sponges on mesophotic reefs with gorgonians relative to reefs without these species. Drawing upon fifteen years of field surveys at five sites in the Caribbean Basin we assessed in situ interactions between gorgonians and sponges to quantify outcomes consistent with competition (i.e., tissue necrosis and overgrowth). Gorgonians were effective competitors against a variety of sponges, and two allelochemicals produced by Ellisella elongata were mechanistically important in interactions with Agelas clathrodes . We also examined invertebrate recruitment patterns near gorgonians to assess their role in facilitating MCE biodiversity. Our results indicate that live gorgonians, Antillogorgia bipinnata and E. elongata , facilitate biodiverse recruitment into MCEs, indicating that this process is governed by more than passive hydrodynamics. Collectively, these data indicate that these gorgonians exhibit both positive and negative ecological interactions (i.e., facilitation and competition, respectively) with sponges, and other taxa. Thus, these gorgonians are FS of MCE communities within the Caribbean Basin that display several traits contributing to the ecological structure of these understudied communities.

Trophic ecology of Caribbean sponges in the mesophotic zone - Keir J. Macartney; Marc Slattery; Michael P. Lesser (Limnology and Oceanography, 2021)
Sponges are a crucial component of Caribbean coral reef ecosystem structure and function. In the Caribbean, many sponges show a predictable increase in percent cover or abundance as depth increases from shallow ( Xestospongia muta , Agelas tubulata , and Plakortis angulospiculatus , and use stable isotope analyses to determine whether shifts in trophic resource utilization along a shallow to mesophotic gradient occurred. Ecological surveys show that all target sponges significantly increase in percent cover as depth increases. Using bulk stable isotope analysis, we show that as depth increases there are increases in the δ 13 C and δ 15 N values, reflecting that all sponges consumed more heterotrophic picoplankton, with low C:N ratios in the mesophotic zone. However, compound‐specific isotope analysis of amino acids (CSIA‐AA) shows that there are species‐specific increases in δ 13 C AA and δ 15 N AA values. Xestospongia muta and P. angulospiculatus showed a reduced reliance on photoautotrophic resources as depth increased, while A. tubulata appears to rely on heterotrophy at all depths. The δ 13 C AA and δ 15 N AA values of these sponges also reflect species‐specific patterns of host utilization of both POM and dissolved organic matter (DOM), its subsequent re‐synthesis, and translocation, by their microbiomes.